Unveiling Patterns of Nomophobia Using Data Mining Techniques - Jabar, Hadeel; Abd, Mustafa S.; Behadili, Suhad Faisal; Ali, Inas (Iraqi Journal of Science, 2024)
Nowadays, almost everyone is glued to their phones. It turns out that the fear of being without your phone has a fancy name: nomophobia. Researchers can now analyze our phone usage using data mining techniques to determine how much we rely on them. They can monitor everything from screen time and social media activity to email habits and app addiction. This information assists us in understanding the impact of technology on our daily lives and may even lead to new interventions or treatment options for those who suffer from nomophobia. Nomophobia, like addiction, progresses through multiple aspects such as initiation, affirmation, need, and dependency. It also manifests in a variety of ways, including socially, physiologically, and physically. The study goal is to look into the nomophobia patterns of the Iraqi academic population (professors, students, and employees) at the University of Baghdad. A descriptive, cross-sectional survey design was used to collect data between 17th October, 2021, and 1st October, 2022. The sample for this study consists of 305 participants. A sociodemographic data sheet, Internet usage profiles, and a nomophobia questionnaire are used to collect information. Thus, data mining techniques have been used to analyze the collected data, hence the concluded results emphasize that there are two major patterns (students group that are annoying during inability to find information on a mobile phone, inability to use it, and inability to check it, and panic when they consume out the credits or hit the monthly data limit, awkward because they couldn’t check their notifications for updates from their connections and online networks, subsequently they would feel weird because they would not know what to do). They exhibit nomophobia, and all the examined individuals have acceptable impacts ofnomophobia.